A forgotten murder - Deveraux, Jude (Deveraux, Jude. Medlar mystery, 2020)
"An English manor home, an unsolved mystery, too many suspects to count -- It's the perfect holiday for romance novelist Sara Medlar. After solving two murder cases in their hometown of Lachlan, Florida, Sara Medlar, her niece Kate and their friend Jack need a change of scenery. Sara arranges for them to visit an old friend of hers in England. Upon arrival at Oxley Manor, a centuries-old estate that has been converted to a luxury hotel, Kate and Jack quickly realize that Sara is up to something. They learn that Sara has also invited a number of others to join them at Oxley. When everyone assembles, Sara lets them know why they are there. Decades earlier, two people ran off together from Oxley and haven't been heard from since -- and Sara wants to solve the case. As the people who were there the night the two went missing, the guests find themselves cast in a live mystery-theater event. In reenacting the events of that night, it becomes clear that everyone has something to hide and no one is safe, especially when the discovery of a body makes it clear that at least one of the people who disappeared was murdered. Sara, Jack and Kate are once again at the heart of a mysterious case that only they are able to solve. But someone is willing to continue to kill to keep the truth about Oxley Manor buried, and none of the guests are safe." -- Provided by publisher.